The Challenges of Surveying Public Opinion in an Emerging Democracy - Ansu-Kyeremeh, K. (International Journal of Public Opinion, 1999)
Based on interviews with political party officials and journalists as well as a content analysis of election poll stories, this paper discusses opinion polling in Ghana's emerging democracy. Highlighted in the discussion are the relevance of surveying public opinion in a neo-democracy and the journalistic reporting of poll results. The paper describes the surveying of public opinion in a political climate in transition from long historical experience of authoritarianism and dictatorship including a period of a ‘culture of silence’, to freedom of expression, as a challenge. In an examination of local ‘polls’ conducted by newspapers during the 1996 presidential and parliamentary elections, it characterizes those exercises as unscientific and inaccurate. Technical details about surveys were mostly missing in the stories, suggesting lack of poll reporting knowledge among journalists as a major challenge. There is an attempt to address these challenges for the purpose of strengthening the enabling role of political polling and journalistic reporting of poll results in Ghana's new democracy. Adequate responses to these challenges would, it is proposed, contribute to a scientific and an objective assessment of issues in political decision–making including measuring voter support for political parties and candidates.